Cross-domain self-authentication based consortium blockchain for autonomous valet parking system - Hua, Lei; Jiang, Haobin; Xiao, Jian; Samie, Mohammad (IEEE, 2022)
This paper proposed a cross-domain self-authentication scheme to address the “information isolated island” problem of users’ identities storage in servers and the “redundant registration problem” of users’ identities for Autonomous Valet Parking (AVP). This scheme adopts a decentralized anonymous authentication method to relieve the authentication center’s service load. Users are segregated into two categories to increase authentication efficiency: inexperienced and regular users. For the former, the paper explores a self-authentication mechanism based on verification parameters. Then, its valid personal information, pseudonym and public key, were stored in a consortium blockchain (PseIDChain) as the transaction records so that they can be securely shared among servers located in different domains. For the latter (regular users), an efficient authentication mechanism, searching users’ personal information on PseIDChain by the smart contract, was proposed. Security proof and simulation results show that the designed scheme has superior security to the existing schemes. Its authentication efficiency is 80.29% and 50.45% higher than the traditional anonymous and batch authentication schemes.
Keywords: Autonomous valet parking; privacy protection; cross-domain authentication; consortium blockchain; pseudonym